2003
DOI: 10.1080/17461390300073504
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of achievement goal orientations in physical activity: A systematic review of research

Abstract: There has been a plethora of studies in the past decade investigating task and ego achievement goal orientations in physical activity settings and how they might be associated with various cognitive, affective and behavioral variables. Although comprehensive narrative reviews of the field exist, no systematic review has been reported except one meta-analysis on only goals and affect. The present paper, therefore, reports a systematic review of 10 correlates of achievement goal orientations across 98 studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
150
5
26

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 193 publications
(194 citation statements)
references
References 97 publications
(81 reference statements)
13
150
5
26
Order By: Relevance
“…Only task orientation positively predicted enjoyment/interest in both contexts. These findings are consistent with the results of past research (Biddle et al, 2003) and suggest that the relationship between task orientation and enjoyment is robust. Previous research has also shown that out of six sources of enjoyment, competence derived through the attainment of personal achievement standards is the most important source for an athlete's enjoyment, whereas competence derived through being better than others and gaining recognition from others is the least important source (Wiersma, 2001).…”
Section: Context Goals and Motivational Responsessupporting
confidence: 83%
See 4 more Smart Citations
“…Only task orientation positively predicted enjoyment/interest in both contexts. These findings are consistent with the results of past research (Biddle et al, 2003) and suggest that the relationship between task orientation and enjoyment is robust. Previous research has also shown that out of six sources of enjoyment, competence derived through the attainment of personal achievement standards is the most important source for an athlete's enjoyment, whereas competence derived through being better than others and gaining recognition from others is the least important source (Wiersma, 2001).…”
Section: Context Goals and Motivational Responsessupporting
confidence: 83%
“…To date, the effects of goal orientations on a variety of motivational responses have been typically examined in the general context of sport, and research has revealed the beneficial effects of task orientation in this context (Biddle et al, 2003). However, athletes constantly make the transition between organised training and competition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations